'We Rise by Lifting Others' Asean Mobility Programme - Siti Sarah, Mohamad Rajimi (2017)
A group of students from Faculty of Mechanical Engineering (FKM) and Faculty of Electrical & Electronics Engineering (FKEE) has successfully organized ‘Final Year Student Asean Mobility Programme 2017. The programme was done involving orphans at Panti Asuhan Al Amin, Bandung, Indonesia with the theme, ‘We Rise by Lifting Others.